Seasonal Variation in Mycorrhizal Community of Different Cerrado Phytophysiomies - Vieira Junior, Wagner Gonçalves; Moura, Jadson Belem de; Souza, Rodrigo Fernandes de; Braga, Ana Paula Maciel; Matos, Diogo Jânio de Carvalho; Brito, Gustavo Henrique Mendes; Santos, José Mateus dos; Moreira, Rodrigo Martins; Dutra e Silva, Sandro (Frontiers in Microbiology, 2020)
Purpose: Understanding the dynamics of mycorrhizal fungi in the Cerrado is fundamental for the adoption of conservation practices and for understanding the resilience of this biome in relation to long periods of drought. Thus, this work aimed to verify the dynamics of the mycorrhizal population in five phytophysiognomies of the Cerrado biome. Methods: The samples were taken from the Chapada dos Veadeiros National Park, a permanent preservation with native Cerrado vegetation without any anthropic influence. The five main phytophysiognomies of the Cerrado biome were chosen, the Campo Limpo, Campo Sujo, Cerrado Strict Sense, Cerradão and Veredas. Rhizospherical soil samples were collected in both the wet and dry seasons. Spore density, mycorrhizal colonization rate, easily extractable glomalin and associated mycorrhizal fungi genera were identified. Results: The values of spore density, mycorrhizal colonization rate and glomalin were higher in the samples performed during the dry season compared to the samples performed in the rainy season. The same behavior was observed when comparing the different phytophysionomies. Conclusion: Mycorrhizal activity is higher in dry periods when compared to rainy periods. There is no specificity of genera of arbuscular mycorrhizal fungi within the cerrado phytophysiognomies